GEOMETRI BERBASIS ETNOMATEMATIKA SEBAGAI INOVASI PEMBELAJARAN DI MADRASAH TSANAWIYAH UNTUK MEMBENTUK KARAKTER ISLAMI - Noor Shofiyati, S.Pd. (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
Many things in life that apply mathematical concepts. Some local cultural heritage and handicrafts such as batik also use mathematical concepts. Approach to learning mathematics through culture will make it easier for children to understand the material. The realm of studies that can be used to show the relationship between culture and mathematics is ethnomatematics. This study aims to describe the learning of transformation geometry based on Yogyakarta batik ethnomatematics and how this learning shapes Islamic character. The research subjects were 24 students of class IX MTsN 9 Bantul. The research data obtained in the form of the results of process observations, responses to student work, and interviews. The results showed that by using Yogyakartan batik ethno-mathematics, students were easier to understand the concept of transformation geometry. And through learning it canshape the character of students.